Validation of the Yoruba Version of the Pain Self-Efficacy Questionnaire in Patients with Chronic Low Back Pain - Opeyemi Idowu (Spine, 2021)
Study Design. Cultural adaptation and psychometric analysis. Objective. This study determined the test–retest reliability, acceptability, internal consistency, divergent validity of the Yoruba pain self-efficacy questionnaire (PSEQ-Y). It also examined the ceiling and floor effects and the small detectable change (SDC) of the PSEQ-Y among patients with chronic low back pain (LBP). Summary of Background Data. There are various indigenous language translations of the PSEQ and none adapted to African language. However, translations of the PSEQ into Nigerian languages are not readily available. Methods. The validity testing phase of the study involved 131 patients with LBP, while 83 patients with LBP took part in the reliability phase. Following the Beaton recommendation for cultural adaptation of instruments, the PSEQ was adapted into the Yoruba language. The psychometric properties of the PSEQ-Y determined comprised: internal consistency, divergent validity, test–retest reliability, and SDC. Results. The mean age of the participants was 52.96±17.3 years. The PSEQ-Y did not correlate with the Yoruba version of Visual Analogue Scale (VAS-Y) scores (r ¼ –0.05; P ¼ 0.59). The values for the internal consistency and the test–retest reliability of the PSEQ-Y were 0.79 and 0.86, with the 95% confidence interval of the test–retest reliability ranging between 0.82 and 0.90. The standard error of measurement (SEM) and the SDC of the PSEQ-Y were 1.2 and 3.3, respectively. The PSEQ-Y had no floor or ceiling effect, as none of the respondents scored either the minimal or maximal scores. Conclusion. This is the first study in Nigeria to culturally adapt PSEQ. The PSEQ-Y showed adequate psychometric properties similar to existing versions. Therefore, the tool can be used to assess pain self-efficacy in clinical and research settings and help to improve the health outcomes of patients chronic LBP.